THE COMMODIFICATION OF THE TRADITIONAL BALINESE WEDDING CEREMONY IN TAMAN PRAKERTI BHUANA, GIANYAR, BALI - Pandji Guritna, Anak Agung Bagus; Pujaastawa, Ida Bagus Gde; Astiti Laksmi, Ni Ketut Puji (E-Journal of Cultural Studies, 2024)
This research seeks to critically examine the commodification of traditional Balinese wedding ceremonies that occur at Taman Prakerti Bhuana, which offers Balinese wedding services in a more attractive and prestigious package. The study aims to understand how sacred cultural practices, rich in spiritual meaning, are transformed into commercial products focused on consumer satisfaction and economic gain. The issues will be addressed by answering the following research questions: (1) What is the form of commodification of traditional Balinese wedding ceremonies at Taman Prakerti Bhuana, (2) Why does the commodification of traditional Balinese wedding ceremonies occur at Taman Prakerti Bhuana, and (3) What are the implications of the commodification of traditional Balinese wedding ceremonies at Taman Prakerti Bhuana. These issues are analyzed using the theories of religious commodification and Bourdieu's theory of practice, employing qualitative research methods. Data collection techniques include literature study, observation, and interviews, followed by interpretative analysis. The research findings indicate that this phenomenon leads to the degradation of traditional values such as "menyama braya," a concept of togetherness and mutual cooperation in Balinese society. The commodification of these ceremonies also impacts the social dynamics of the local community, reducing active community participation and eroding the spirit of mutual cooperation. Ultimately, this study highlights the challenges faced in preserving Balinese culture, where traditional rituals that undergo changes to meet market demands risk losing their authenticity and original meaning. Keywords : Commodification, Traditional Balinese Wedding Ceremony, Taman Prakerti Bhuana